5-Fluorouracil/irinotecan induced lethal toxicity as a result of a combined pharmacogenetic syndrome: report of a case. Issue 5 (27th April 2005) - Steiner, M; Seule, M; Steiner, B; Bauer, I; Freund, M; Köhne, C H; Schuff-Werner, P
Abstract : Combination cancer chemotherapy induced toxicity can be associated with combined pharmacogenetic syndromes. Dihydropyrimidine dehydrogenase (DPD) is the principal enzyme involved in the catabolic detoxification of 5-fluorouracil (5FU). A heterozygous G > A transition at the 5′ splicing donor consensus sequence in intron 14 leading to exon 14 skipping (IVS14+1 G > A, DPYD*2A) with partial loss of enzyme activity may be partly responsible for 5FU induced toxicity, whereas irinotecan associated toxicity may in part be explained by an aberrant UGT1A1 promoter (TA)n genotype underlying Gilbert's syndrome with reduced liver glucuronidation activity. This report describes a 44 year old white woman who suffered from severe gastrointestinal and haematological toxicity while undergoing 5FU24h /folinic acid/irinotecan treatment for adenocarcinoma of the sigmoid colon. Despite appropriate supportive treatment, her condition rapidly deteriorated and led to death. Molecular analysis revealed a hitherto undescribed combined pharmacogenetic syndrome, consisting of heterozygosity for the DPD IVS14+1 G > A mutation and UGT1A1 (TA)6/7 heterozygosity, which probably contributed to the fatal outcome in this patient.